1996
DOI: 10.1046/j.1365-2249.1996.42748.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating antibodies against rat parotid gland M3 muscarinic receptors in primary Sjögren’s syndrome

Abstract: SUMMARYIn this study we demonstrate that IgG present in the sera of patients with primary Sjögren's syndrome (PSS) could bind and activate muscarinic acetylcholine receptors (mAChRs) of rat parotid gland. These antibodies were able to inhibit in a non-competitive manner the binding of 3 H-quinuclidinyl benzilate (QNB) to mAChRs of purified rat parotid gland membranes. Moreover, IgG from PSS could modify biological effects mediated by mAChR activation; i.e. decrease cAMP, increase phosphoinositide turnover with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
146
0
5

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(156 citation statements)
references
References 26 publications
5
146
0
5
Order By: Relevance
“…The reversibility of the binding observed when mouse or human submandibular acinar cells are exposed to SS IgG or rabbit polyclonal anti-M 3 R is intriguing since it confirms the previous findings in Ig -null mice (71) but is contradictory with data obtained from smooth muscle bioassay (15,62,64) and radioligand binding studies (14,73). In myasthenia gravis it is established that, in vitro, the reversibility of the interaction between the autoantibodies and the nicotinic cholinergic receptors is highly dependent on the length of time of exposure and the concentration of the autoantibody (85).…”
Section: Induction Of Cholinergic Hyperresponsiveness By Passive Transupporting
confidence: 47%
See 3 more Smart Citations
“…The reversibility of the binding observed when mouse or human submandibular acinar cells are exposed to SS IgG or rabbit polyclonal anti-M 3 R is intriguing since it confirms the previous findings in Ig -null mice (71) but is contradictory with data obtained from smooth muscle bioassay (15,62,64) and radioligand binding studies (14,73). In myasthenia gravis it is established that, in vitro, the reversibility of the interaction between the autoantibodies and the nicotinic cholinergic receptors is highly dependent on the length of time of exposure and the concentration of the autoantibody (85).…”
Section: Induction Of Cholinergic Hyperresponsiveness By Passive Transupporting
confidence: 47%
“…Findings of radioligand binding studies have suggested that serum from a large proportion of patients with SS, but not from controls, contains IgG antibodies that can noncompetitively bind to the M 3 R of rat parotid gland (14) or rat exorbital lacrimal gland membranes (73), as well as salivary IgA antibodies that can noncompetitively bind to the M 3 R of rat parotid salivary gland membranes (74). While these data suggest that antimuscarinic antibodies may have a pathologic role in SS, they do not conclusively demonstrate that the interaction is exclusively with M 3 R. This is because experimental differentiation between the muscarinic receptor subtypes present in a tissue is difficult since there are no specific selective antagonists available and, in rodent salivary glands, M 3 R, M 4 R (75), and M 1 R (76) are all present.…”
Section: Induction Of Cholinergic Hyperresponsiveness By Passive Tranmentioning
confidence: 99%
See 2 more Smart Citations
“…33 A reduced tear secretion, consequent to reduced corneal sensitivity, could also be in relation with an impairment in the parasympathetic control of lachrymal gland, as demonstrated in other exocrine gland, 34,35 as a consequence of the presence of anti M3 muscarinic receptors 36 independently from the concurrent presence of anti-SSA and anti-SSB, 37 as it has been demonstrated in an animal model. 38 A reduced tear clearance rate results in accumulation of corneal metabolism products, including the inflammatory cytokines present in the tear fluid of SS-I patients 39,40 maintaining the ocular surface inflammation within a vicious circle.…”
Section: Eyementioning
confidence: 99%